The prognostic significance of fibroblast growth factor-23 in predicting complications of type 2 diabetes mellitus, especially when associated with obesity - Marchenko , Anastasia; Pasiieshvili , Lyudmila (The Ukrainian Scientific Medical Youth Journal, 2024)
type 2 Diabetes Mellitus (T2DM) is considered a global health problem with an exceptionally high economic burden not only for families but also for countries overall. In 90-95% of T2DM cases, varying degrees of obesity are observed. One aspect contributing to complications in T2DM involves musculoskeletal system impairment, specifically alterations in bone mineral density (BMD), indicative of bone architecture disruption, leading to secondary osteoporotic conditions. Fibroblast growth factors (FGFs), known for their regulatory influence on metabolism, are identified as mechanisms activated in T2DM. Within this group, fibroblast growth factor 23 (FGF-23) is acknowledged. In individuals with T2DM and excess weight or obesity, conditions conducive to increased FGF-23 synthesis are established, contributing to disturbances in mineral metabolism. Therefore, our study aimed to investigate the content and role of FGF-23 in the development of secondary osteoporosis in T2DM patients with concurrent obesity. A total of 103 patients with type 2 diabetes were involved, with 83 cases featuring elevated body weight or obesity (main group). To assess the impact of obesity on FGF-23 changes, a comparison group of 20 T2DM patients with normal body weight (NBW) was formed. The average age of patients with comorbid conditions was 43±4.6 years, and for those with isolated T2DM, it was 44.1±2.1 years. The average duration of T2DM across groups ranged from 1 to 13 years (6.7±2.4 years on average). Control FGF-23 values were obtained from a group of 20 practically healthy individuals of similar age and gender. The diagnosis of T2DM was confirmed according to the Unified Medical Assistance Protocol "Diabetes Mellitus" (Order of the Ministry of Health of Ukraine dated December 21, 2012, No. 1118). Thus, all examined T2DM patients were in the subcompensation stage with a moderate degree of disease severity. The presence and severity of obesity were assessed according to the International Diabetes Federation (IDF, 2005) criteria based on the body mass index (BMI) calculation using the Ketle formula. In the examination of 83 T2DM patients with obesity, a probable increase in fibroblast growth factor 23 (FGF-23) in serum was determined, correlating with osteoporotic changes in dual-energy X-ray absorptiometry. Therefore, FGF-23 can be utilized as a marker for bone mineral density status and control of treatment measures.